The role of emotional response to music, media influence, and nationalistic themes on Chinese national identity - Danhe, Zheng; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of emotional response to music, media influence, and nationalistic themes in music on Chinese national identity. Utilizing a quantitative approach, the study sampled 385 participants and employed Pearson correlation and multiple regression analyses to explore the relationships between these variables. Results revealed that nationalistic themes in music emerged as the strongest predictor of national identity, followed closely by media influence and emotional response to music. These findings highlight the critical role that both music and media play in fostering a strong sense of national identity, particularly in a context where cultural and political narratives are tightly intertwined. The study suggests that reinforcing nationalistic themes in cultural expressions,. alongside media campaigns promoting national pride, can further strengthen collective national identity. These insights provide valuable implications for policymakers, educators, and media creators aiming to bolster national unity and cultural heritage in China.